1997
DOI: 10.1152/jn.1997.78.4.2226
|View full text |Cite
|
Sign up to set email alerts
|

Object Representation in the Ventral Premotor Cortex (Area F5) of the Monkey

Abstract: Visual and motor properties of single neurons of monkey ventral premotor cortex (area F5) were studied in a behavioral paradigm consisting of four conditions: object grasping in light, object grasping in dark, object fixation, and fixation of a spot of light. The employed objects were six different three-dimensional (3-D) geometric solids. Two main types of neurons were distinguished: motor neurons (n = 25) and visuomotor neurons (n = 24). Motor neurons discharged in association with grasping movements. Most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
400
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 633 publications
(427 citation statements)
references
References 25 publications
27
400
0
Order By: Relevance
“…Accordingly, the left superior temporal gyrus is activated when subjects imitate the actions of other individuals , more than when the subject's own actions are imitated by others . Activations within the inferior part of the frontal gyrus, and especially in Brodmann area (BA) 44 and 45, were likewise reported during observation [Decety et al, 1997;Grafton et al, 1996;Rizzolatti et al, 1996b], imagination and execution [Gerardin et al, 2000] of gestures, imitation and preparation of imitation [Iacoboni et al, 1999;Krams et al, 1998], imagery of motion and of hand movements [Binkofski et al, 2000;Parsons et al, 1995], object manipulation [Binkofski et al, 1999] and visual perception of tool and manipulatable object [Chao and Martin, 2000;Grèzes and Decety, 2002;Murata et al, 1997]. Others have found that the bilateral premotor cortex is activated in a somatotopic manner during both observation and execution of various mouth, hand, and foot actions [Buccino et al, 2001].…”
Section: Output Praxicon and Gestural Representationsmentioning
confidence: 77%
“…Accordingly, the left superior temporal gyrus is activated when subjects imitate the actions of other individuals , more than when the subject's own actions are imitated by others . Activations within the inferior part of the frontal gyrus, and especially in Brodmann area (BA) 44 and 45, were likewise reported during observation [Decety et al, 1997;Grafton et al, 1996;Rizzolatti et al, 1996b], imagination and execution [Gerardin et al, 2000] of gestures, imitation and preparation of imitation [Iacoboni et al, 1999;Krams et al, 1998], imagery of motion and of hand movements [Binkofski et al, 2000;Parsons et al, 1995], object manipulation [Binkofski et al, 1999] and visual perception of tool and manipulatable object [Chao and Martin, 2000;Grèzes and Decety, 2002;Murata et al, 1997]. Others have found that the bilateral premotor cortex is activated in a somatotopic manner during both observation and execution of various mouth, hand, and foot actions [Buccino et al, 2001].…”
Section: Output Praxicon and Gestural Representationsmentioning
confidence: 77%
“…Our results extend this literature by showing that in humans bilateral BA44/45 exhibits a differential activation pattern in association with different grasp types and supports the parallelism between macaque and humans in grasp type selectivity at the level of premotor cortices (Murata et al. 1997; Carpaneto et al. 2011).…”
Section: Discussionmentioning
confidence: 99%
“…On one side, both F5 and AIP neurons code for reach‐to‐grasp actions (Murata et al. 1997, 2000). However, AIP neurons seem to represent the entire action, whereas F5 neurons seem to be concerned with a particular segment of it (Rizzolatti et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have suggested that this activity is not about tools per se, but instead appears when participants make judgments about manipulable objects (including fruits and vegetables) as compared to objects that are typically viewed without motoric engagement (Gerlach et al, 2002;Kellenbach et al, 2003). The left ventral premotor locus in these hemodynamic studies is also considered to be the human analogue of monkey area F5, in which neurons respond during both performance and observation of actions (Murata et al, 1997;see Grezes and Decety, 2001 for review of human studies suggesting a parallel result). In the current results, the commonality of the real-object/pantomime difference after Perform, Watch, and Imagine encoding strongly suggests an origin in left premotor cortex.…”
Section: Pantomimed Action Versus Actions With Real Objectsmentioning
confidence: 99%